(untitled) (Research, Society and Development, 2023)
The present study has as its theme “The mental health care of public school teachers in Manaus/AM.” It is understood that the teacher can be considered within society in general, a relevant professional, as he works as a guide for a good part of the lives of several people. According to the International Labor Organization, the teaching profession is considered one of the most stressful, and through studies it is possible to see that the number of professionals in the educational area who have some pathology related to their mental health has been growing. . Given this context, it is understood that teaching nowadays is becoming one of the most exhausting and stressful activities, considering that it affects not only the mental health, but also the physical health of teachers. Therefore, the objective of this project is to analyze the mental health care of teachers in public schools. Due to this need, the present study adopts a qualitative methodology based on a bibliographical review to analyze situations that may be impacting on the mental health of teachers. As a result, it was shown that many situations can negatively affect the mental health of education professionals, causing their health status to be temporarily altered and causing illness or other suffering and mental disorders that significantly affect their performance. work and performance.